Evaluation of the influences of solution path length and additives concentrations on the solar photo-Fenton degradation of 4-chlorophenol using multivariate analysis - Trovo, Alam G.; Paterlini, Willian C.; Nogueira, Raquel Fernandes Pupo [UNESP] (Elsevier B.V., 2006)
This study reports the photodegradation of 4-chlorophenol (4-CP) in aqueous solution by the photo-Fenton process using solar irradiation. The influence of solution path length, and Fe(NO3)(3) and H2O2 concentrations on the degradation of 4-CP is evaluated by response surface methodology. The degradation process was monitored by the removal of total organic carbon (TOC) and the release of chloride ion. The results showed a very important role of iron concentration either for TOC removal or dechlorination. on the other hand, a negative effect of increasing solution path length on mineralization was observed, which can be compensated by increasing the iron concentration. This permits an adjustment of the iron concentration according to the irradiation exposure area and path length (depth of a tank reactor). Under optimum conditions of 1.5 mM Fe(NO3)(3), 20.0 mM H2O2 and 4.5 cm solution path length, 17 min irradiation under solar light were sufficient to reduce a 72 mg C L-1 solution of 4-CP by 91 (c) 2006 Elsevier B.V. All rights reserved.
Keywords: advanced oxidation processes; degradation; 4-chlorophenol; experimental design